G165 Using video vignettes and doctors' responses to assess the efficacy of paediatric simulation. (12th March 2018) - Malley, M; Ko, M; Monaghan, M
Abstract : Aims: Paediatric simulation is an established part of medical student training. However there remain many ways to assess its efficacy. We aimed to assess the efficacy of a simulation programme using video-based clinical vignettes and comparing student responses to established paediatric doctors. Method: We created a paediatric simulation programme for 87 fifth year medical students. The programme involved two-hour theory session followed by a two-hour high fidelity simulation in groups of five. Twelve clinical vignettes were created based on the videos from 'Spotting The Sick Child' online resource (with permission). The students stated how sick they thought the child was for each scenario on a scale of 1 to 10, where 10 was 'immediate PICU admission' and 1 was 'immediate discharge'. This quiz was carried out pre- and post-course. Twenty post- MRCPCH paediatricians carried out the same quiz. The average of their scores was considered the 'gold standard'. The deviation between the paediatrician and student scores was calculated both pre- and post-programme. Students also rated their confidence level in assessing and managing the cases before and after the programme. Results: Overall, students' responses were significantly closer to the doctors' mean post session (p=0.0048). This was particularly pronounced in respiratory distress, dehydration and DKA scenarios. The average value of students' confidence level for assessing paediatric emergencies pre- and post-simulation were 2.91/5 and 3.58/5, respectively (p<0.001). Similarly their reported confidence in managing the emergencies was 2.36/5 pre-session and 3.36/5 post-session (p<0.000005). Conclusion: Video vignettes provided a novel approach to assessing the efficacy of a paediatric simulation programme. Students' responses more closely correlated with more experienced specialist physicians after the session compared to pre-session. The convergence of the paediatricians' and students' scores post-session was validated by the students' self-reported increased confidence level in assessing and managing the scenarios post-session. This supports the utility of this method for assessing the clinical educational efficacy of paediatric simulation programmes.